Monitoring and Efficiency in Governance: A Measure for Sustainability in the Islamic Banking Industry - Awais, Muhammad; Ullah, Naeem; Sulehri, Numair Ahmad; Thas Thaker, Mohamed Asmy bin Mohd; Mohsin, Muhammad (Frontiers in Psychology, 2022)
Abstract: Corporate governance is a set of rules, regulations, procedures, processes, and practices based on which an organization is controlled and directed. However, there is a room to improve monitoring systems for Islamic banking operations. The standardized measures can improve Islamic banking operations efficiency that can lead to sustainable performance. The aim of the present study was to know about the monitoring methods of Islamic banking, standardized measures for better performance, individual’s aptitude towards Islamic financial markets, risk propensity, and level of efficiency of the Islamic banking industry in Pakistan and Malaysia. This study uses a self-developed Semi-structured scale (based on literature and expert interviews) after content and context validity to get a wide range of diversified information. In Pakistan and Malaysia, individuals’ perceptions are different because of differences in banking environment and preferences. Eventually, the Islamic banking growth rate may differ in Pakistan and Malaysia. Thus, there should be regular monitoring to improve banking performance. Similarly, standardized measures for Islamic banking operations and governance performance in Pakistan and Malaysia will result in sustainable performance. The antecedents of Islamic corporate governance can be improved to enhance banking performance, which helps individuals make decisions based on available products information. The business growth of the banking industry is based on convenient monitoring policies, standardized performance measures, and, most importantly, excellent corporate governance mechanisms. The improved monitoring measures will further enhance the business operations.